Distribusi Spasial Kualitas Air Sumur di Sekitar Rumah Sakit St. Carolus Borromeus Kupang - Leonardus Lewa Leko; Oktavina GLP. Manulangga; Madalena Da Costa (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
Well water is one of the water sources that is still used by the community for consumption and to fulfill other household needs. Community well water near the Carolus Borromeus Hospital has the potential to become contaminated. This research was conducted to analyze the spatial distribution of well water quality around St. Carolus Borromeus Kupang. This study aims to determine the quality standards of well water around the St. Carolus Borromeus Kupang and determine the spatial distribution pattern of groundwater around St. Carolus Boromeus. The method used in this research is taking samples then analyzing them in the laboratory and then comparing the results of physical, chemical and biological analysis with the applicable water quality standards according to their intended use. The spatial distribution pattern uses the parameter distribution pattern analysis method. The research results show that based on physical, chemical and biological analysis, in hospital outlet liquid waste there are several parameters that meet quality standards, but there are parameters such as Total coliform that do not meet quality standards. The results of parameter analysis in SG1 well water which is close to the hospital, several parameters meet quality standards, but the Fecal Coliform parameter does not meet quality standards for hygienic and sanitation purposes. The level of spread of contamination from organic matter and bacteria in groundwater is influenced by the type of soil, slope and direction of groundwater flow. The lower an area, the higher it is